Some scientific issues related to biological resource use and management toward sustainable development of marine economy in the costal provinces in South Central Vietnam - Tuan, Vo Si; Long, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2019)
Based on referring recent target scientific issues related to sustainable development in the world and considering practices of economic development in the provinces of South Central Vietnam, some issues were selected for analyses in terms of concepts, needs and orientations applicable to the region. They include, inter alia: Economic valuation of marine ecosystems; Important levels of habitats in coastal ecosystems; Rehabilitation and restoration of degraded resources; Natural hazards - prevention and resilience; Marine protected areas and fisheries enhancement; Deoxygenation in marine environment and economic losses in fisheries.